The identity of Islam in project development and the public realm: resisting global mimicry and returning to contextualised inventiveness - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Md Sharif, Harlina; Hamat, Sufian (Springer, 2019)
Whenever the identity of Islam in the built environment is called for as part of identitymaking in the development of new public buildings including governmental institutions, general urban-scape of towns, interpretations of this requirement have demonstrated a range of cosmetically inclined cut-and-paste imageries with externally imported range of facade solutions, expressions, vocabulary and formal themes rather than localised interpretations and inventions. These imageries, which are often proposed and built, comprise of the mere mimicry of Arab-Islamic forms and traditions – reflecting an imposed hegemony linked to Middle Eastern past historiographies and origins of Islam. Due to pressure of project development, to fulfil the implicit requirement, mimicry is often being resorted to inform and facade systems, including roof forms and urban design elements. Public built expression inevitably veers to a certain cultural image which is portrayed as the "true" expression of Islam. The paper argues that the ethical and philosophical foundations of Islam calls for a complete reworking of such „Islamic‟ meanings and a reworking on identities based on localised contextualised "inventive" and "imaginative" approach in public buildings. This include highlighting elements derived from local, natural and cultural resources including histories and past ingenuities in compliance to Shariah. The "Islam" in built environment is a global expression of multicultural efflorescence rather than simply a “cosmetic” imposition of mono-ethnic or romantic images from Arab Islamic past models. The paper highlights how built forms and spaces can have spiritual inferences yet be universal, without specific ethnic reference. Islam expansion was a global physical phenomena of syncretised solutions in past cities and buildings as far as China without imposing alien forms onto the local public realm nor the urban-scape. Through content analysis, and survey of the stakeholders in the industry and society with Malaysia as the case study, the research aims to highlight series of suggestive solutions representing the contextual and syncretic approach, ranging from overall forms, structures, decorative motifs and spaces in range of holistic juxtaposition as urban solutions unique to the Malaysian Muslim society as regional identity.